Welcome to Westonci.ca, the ultimate question and answer platform. Get expert answers to your questions quickly and accurately. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
To solve the system of linear equations:
[tex]\[ \begin{array}{l} 2x + 7y = -1 \\ 4x - 3y = -19 \end{array} \][/tex]
we will use the method of elimination step by step.
### Step 1: Align the equations
[tex]\[ \begin{array}{l} 2x + 7y = -1 \quad \text{(Equation 1)} \\ 4x - 3y = -19 \quad \text{(Equation 2)} \end{array} \][/tex]
### Step 2: Eliminate one variable
First, we want to eliminate \( x \). We can do this by making the coefficients of \( x \) the same in both equations. To do this, we can multiply Equation 1 by 2.
[tex]\[ 4x + 14y = -2 \quad \text{(Equation 3, derived from Equation 1)} \][/tex]
Now we have:
[tex]\[ \begin{array}{l} 4x + 14y = -2 \quad \text{(Equation 3)} \\ 4x - 3y = -19 \quad \text{(Equation 2)} \end{array} \][/tex]
### Step 3: Subtract the equations
Next, subtract Equation 2 from Equation 3 to eliminate \( x \):
[tex]\[ (4x + 14y) - (4x - 3y) = -2 - (-19) \][/tex]
Which simplifies to:
[tex]\[ 4x + 14y - 4x + 3y = 17 \][/tex]
[tex]\[ 17y = 17 \][/tex]
### Step 4: Solve for \( y \)
Divide both sides by 17:
[tex]\[ y = 1 \][/tex]
### Step 5: Substitute \( y \) back into one of the original equations
Let’s substitute \( y = 1 \) into Equation 1:
[tex]\[ 2x + 7(1) = -1 \][/tex]
[tex]\[ 2x + 7 = -1 \][/tex]
[tex]\[ 2x = -1 - 7 \][/tex]
[tex]\[ 2x = -8 \][/tex]
[tex]\[ x = -4 \][/tex]
### Step 6: Write the solution as an ordered pair
Thus, the solution to the system of equations is:
[tex]\[ (x, y) = (-4, 1) \][/tex]
[tex]\[ \begin{array}{l} 2x + 7y = -1 \\ 4x - 3y = -19 \end{array} \][/tex]
we will use the method of elimination step by step.
### Step 1: Align the equations
[tex]\[ \begin{array}{l} 2x + 7y = -1 \quad \text{(Equation 1)} \\ 4x - 3y = -19 \quad \text{(Equation 2)} \end{array} \][/tex]
### Step 2: Eliminate one variable
First, we want to eliminate \( x \). We can do this by making the coefficients of \( x \) the same in both equations. To do this, we can multiply Equation 1 by 2.
[tex]\[ 4x + 14y = -2 \quad \text{(Equation 3, derived from Equation 1)} \][/tex]
Now we have:
[tex]\[ \begin{array}{l} 4x + 14y = -2 \quad \text{(Equation 3)} \\ 4x - 3y = -19 \quad \text{(Equation 2)} \end{array} \][/tex]
### Step 3: Subtract the equations
Next, subtract Equation 2 from Equation 3 to eliminate \( x \):
[tex]\[ (4x + 14y) - (4x - 3y) = -2 - (-19) \][/tex]
Which simplifies to:
[tex]\[ 4x + 14y - 4x + 3y = 17 \][/tex]
[tex]\[ 17y = 17 \][/tex]
### Step 4: Solve for \( y \)
Divide both sides by 17:
[tex]\[ y = 1 \][/tex]
### Step 5: Substitute \( y \) back into one of the original equations
Let’s substitute \( y = 1 \) into Equation 1:
[tex]\[ 2x + 7(1) = -1 \][/tex]
[tex]\[ 2x + 7 = -1 \][/tex]
[tex]\[ 2x = -1 - 7 \][/tex]
[tex]\[ 2x = -8 \][/tex]
[tex]\[ x = -4 \][/tex]
### Step 6: Write the solution as an ordered pair
Thus, the solution to the system of equations is:
[tex]\[ (x, y) = (-4, 1) \][/tex]
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.